Fenomena tenaga kerja perempuan pada Usahatani bawang merah (Studi Kasus Tenaga Kerja Bawang Merah Di Desa Janggurara Kecamatan Baraka Kabupaten Enrekang) - Adeti Nur Rahma; Irmayani Irmayani; Nurhaedah Nurhaedah (Universitas Muslim Maros, 2024)
Women's involvement in shallot farming is quite large, they work in several production and post-harvest farming activities. In the world of agriculture, women not only play the role of housewives, but many women are also found who play a role or directly make a real contribution to the farming business carried out by the family itself. Farming activities carried out by female farmers are influenced by the amount of work time. The phenomenon of female labor in shallot farming can be a driving or inhibiting factor in optimizing the farming carried out. In this research, the role of women can be seen from two categories, namely the role of women as labor in decision making in onion farming and the role of women as labor in increase in onion farming income. The aims of this research are: 1) To determine the role of women as workers in decision making in shallot farming in Janggurara Village, 2) To determine the role of women as labor in increasing the income of shallot farming in Janggurara Village. This research uses descriptive qualitative and quantitative research methods, because in its implementation qualitative data is obtained through descriptions of interviews, questionnaires, observations, literature studies, and quantitative data is obtained in the form of numbers which are analyzed using mathematical formulas, the data used is primary and secondary data. There were 70 samples in this study which were then processed using Microsoft Excel, and analyzed using the Likert Scale analysis technique. From the research results, it was obtained: 1) As many as 7% of female farmers agreed that shallot farming managed by women was able to help farmers in making decisions regarding farming activities so that the profits they could obtain were greater than other agricultural commodities. 2) as many as 7% said that female farmers have a big influence in increasing income from shallot farming because through collaboration between women and men, they are able to create smooth farming activities and the obstacles they face can be resolved.